Preparation method and application of protective film with blue light prevention function
By using the combination of aluminum-doped zinc oxide, N-doped titanium dioxide and dioxins as blue light absorbers in the anti-blue light film, the problem of excessive shielding of beneficial blue light by the existing anti-blue light film is solved, effective filtration of harmful blue light and retention of beneficial blue light is achieved, color shift problem is weakened, and the safety and light transmittance of the protective film is improved.
Patent Information
- Application Number
- CN202411917183.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
While filtering harmful blue light, existing anti-blue light films often over-block blue light bands that are beneficial to the human body, resulting in color shifts and other problems, and some blue light absorbers have safety hazards.
The combination of aluminum-doped zinc oxide, N-doped titanium dioxide and dioxins is used as the blue light absorber. Through the overlap and combination of the light absorption ranges of different materials, the absorption of harmful blue light and the retention of beneficial blue light are achieved, which reduces the color shift and improves the safety of the protective film.
Effective filtering of harmful blue light and retention of beneficial blue light are achieved, which weakens the color shift problem and improves the safety and light transmittance of the protective film.
Smart Images

Figure BDA0005207086300000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical films, and in particular relates to a preparation method and application of a protective film with a blue light protection function. Background Art
[0002] As electronic products are used more and more frequently in people's lives, people are increasingly exposed to the blue light from electronic product displays, which inevitably affects people's health. According to research, the blue light emitted by LED screens can cause certain damage to vision. In order to prevent the hidden dangers to vision health caused by the displays of electronic devices such as mobile phones and computers, many companies have developed anti-blue light protective films to block the radiation of high-energy short-wave blue light to the human body.
[0003] Blue light blocking film mainly blocks blue light by absorbing or reflecting blue light. Blue light blocking film often combines blue light blocking function with other functional layers on a thin film. By controlling the blocking rate of blue light in a specific band, it can minimize the color change and color deviation of the display device and maintain a certain brightness. However, there are many problems in the actual use of blue light blocking film.
[0004] Blue light refers to electromagnetic waves with a wavelength between 400-500nm in the visible spectrum. Blue light is divided into beneficial and harmful types. Blue light with a wavelength between 415 and 455 nanometers is short-wave harmful blue light. Harmful blue light can penetrate the lens and reach the retina directly due to its shorter wavelength and higher energy, causing damage to retinal pigment epithelial cells, and then causing eye diseases such as macular degeneration and cataracts. It needs to be protected. Blue light between 480 and 500 nanometers has a function of adjusting biological rhythms. Sleep, mood, memory, etc. are all related to it, which is beneficial to the human body. Some current anti-blue light products will excessively block blue light and block the blue light bands that are beneficial to physiological regulation. This may cause color deviation, yellowing of the protective film, and other problems. It is necessary to balance the needs of filtering harmful blue light and retaining beneficial blue light.
[0005] Most blue light-blocking films contain blue light absorbers, which absorb blue light to achieve the blue light filtering effect. There are three main types of blue light absorbers: organic, organic-inorganic hybrid, and inorganic. The blue light filtering effect decreases and the stability increases. Most organic blue light absorbers are organic dyes, and the heavy metal components in organic dyes may pose a safety hazard. If the human body is exposed to them for a long time, it will cause harm to health and may cause environmental pollution after being discarded. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a protective film with anti-blue light function, which can improve the safety of the protective film while strictly controlling the blue light filtering wavelength range, filter harmful blue light and retain beneficial blue light, and reduce color deviation.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a protective film with a blue light protection function, comprising the following steps:
[0009] Step 1: coating the wear-resistant layer slurry on the upper surface of the transparent substrate, and obtaining the wear-resistant layer after curing;
[0010] Step 2: coating the anti-blue light layer slurry on the lower surface of the transparent substrate, and obtaining the anti-blue light layer after curing;
[0011] Step 3: coating the surface of the anti-blue light layer with an adhesive layer slurry, and covering the surface of the adhesive layer with a release film to obtain a protective film with anti-blue light function;
[0012] The anti-blue light layer slurry comprises the following raw materials by mass percentage:
[0013] Aluminum-doped zinc oxide 7-15%, N-doped titanium dioxide 2-6%, diosgenin 1-3%, photoinitiator 5-15%, dispersant 4-10%, acrylate 30-40%, defoamer 0.1-0.5%, and the balance is solvent.
[0014] In the slurry, aluminum-doped zinc oxide, N-doped titanium dioxide and diosgenin are used as blue light absorbers, among which aluminum-doped zinc oxide can achieve the absorption of ultraviolet and part of blue light in a wide range below 420nm, and N-doped titanium dioxide can achieve the absorption of ultraviolet and harmful blue light in a narrow range of 300-450nm by doping red shift. Diosgenin is an important basic raw material for the production of steroid hormone drugs. It is prepared from Sichuan earthworm raw medicine or turmeric as raw material. It is a white crystal. The absorption wavelength of diosgenin is mainly concentrated at 410nm and 452nm. The blue light absorber in the anti-blue light slurry is a combination of inorganic materials and natural organic matter. It is non-toxic and has high safety. The inorganic material has high stability. Most of its materials are light-colored, which will not affect the main color of the anti-blue light layer. The transmittance is high, and through the combination of materials with different maximum absorption peaks, the focus on the absorption of ultraviolet and harmful blue light wavelength ranges is achieved, and the absorption of beneficial blue light is weak, which can balance the filtering of harmful blue light and the retention of beneficial blue light.
[0015] Furthermore, the transparent substrate is one of a PET film, a PC film, a TPU film and a PMMA film.
[0016] Furthermore, the preparation steps of the aluminum-doped zinc oxide are as follows:
[0017] Aluminum sulfate 18hydrate solution and zinc sulfate heptahydrate solution were mixed, and ammonia solution was added dropwise to the mixed solution under constant temperature stirring until the pH value of the system was 7-7.5. After the addition was completed, the mixture was allowed to react for 2-4 hours, filtered, washed, and dried, and ground to obtain aluminum-doped zinc oxide precursor powder, which was then calcined at high temperature to obtain aluminum-doped zinc oxide.
[0018] Aluminum-doped zinc oxide is prepared by chemical coprecipitation. Generally, the ultraviolet-visible absorption peak of zinc oxide is 320-400nm. When aluminum replaces the lattice position of zinc, due to Al 3+ The radius is smaller, the Al-O bond is stronger than the Zn-O bond, and the high-valent Al 3+ Replace low-priced Zn 2+ In order to maintain charge balance, oxygen vacancies are inevitably generated, and the UV-visible light activity of the material increases with the increase of oxygen vacancies in the material. Therefore, the light absorption edge of the UV-visible spectrum of Al-doped ZnO will red-shift, and its absorption range can be extended to around 420nm, realizing the absorption of short-wave blue light.
[0019] Furthermore, the mass of the aluminum element in the mixed solution is 0.5-1% of the mass of the zinc element.
[0020] The amount of aluminum doped in aluminum-doped zinc oxide is crucial. When the amount of aluminum doping is too small, it replaces Zn 2+ The amount of aluminum doping is small, and the oxygen vacancies formed are correspondingly small. The red shift effect is not obvious, and the absorption range cannot reach the harmful blue light band. When aluminum doping is excessive, aluminum is more inclined to form ZnAl2O4 spinel compounds with zinc oxide rather than replacing Zn 2+ Position, its effect of promoting blue light absorption will be significantly reduced.
[0021] Furthermore, the temperature of the constant temperature stirring is 70-80°C, the temperature of the high temperature calcination is 1000-1300°C, and the calcination temperature is 6-10h.
[0022] The calcination temperature affects the final content of aluminum doping. When the calcination temperature is too low, aluminum ions cannot enter the zinc oxide lattice. Increasing the calcination temperature allows more aluminum ions to enter, but when the temperature is too high, it will lead to larger grain size, smaller specific surface area, and weakened light absorption capacity.
[0023] Furthermore, the preparation steps of the N-doped titanium dioxide are as follows:
[0024] Titanium dioxide is dispersed in water, urea is added, and after ultrasonic dispersion, it is heated to 200-250° C. and reacted for 2-4 hours. The mixture is cooled to room temperature, filtered, washed, dried, and calcined at high temperature to obtain N-doped titanium dioxide.
[0025] Titanium dioxide has a very strong absorption capacity in the ultraviolet spectrum, especially in the wavelength range of 200-400 nanometers, but its absorption capacity in the visible light region (i.e. 400-700nm) is weak and cannot absorb blue light. Since the radius of N and O atoms is very similar, it is easy to replace oxygen elements. The impurity energy level introduced by N doping and the oxygen vacancy defects generated are of great significance to improving the visible light response of titanium dioxide. It reduces the excitation energy by affecting the TiO2 band structure, causing its absorption edge to redshift, achieving visible light response, narrowing the TiO2 bandgap width, and improving its visible light activity.
[0026] Furthermore, the molar ratio of titanium dioxide to urea is 1:1-3.
[0027] The amount of nitrogen doping has a great influence on the light absorption capacity of the material. As the nitrogen content increases, the infrared absorption edge of TiO2 will red-shift accordingly, but too high or too low a nitrogen content will lead to a decrease in visible light absorption efficiency and a weakening of the light absorption capacity. When the molar ratio of titanium dioxide to urea is 1:1-3, the absorption edge of N-doped titanium dioxide can be ensured to be red-shifted to around 450nm.
[0028] Furthermore, the calcination temperature is 300-600° C., and the calcination time is 1-4 hours.
[0029] The increase of calcination temperature is conducive to the insertion of nitrogen into the titanium dioxide lattice. Too high calcination temperature will cause an increase in the loss of nitrogen doping, an increase in particle size, and a decrease in light absorption capacity.
[0030] Furthermore, the photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, 2,2-dimethoxy-2-phenylacetophenone, and 2,2-dimethoxyacetophenone.
[0031] Phenyl ketone photoinitiators can decompose under ultraviolet light to produce benzene free radicals, thereby initiating monomer polymerization. They have efficient photoinitiation ability and excellent stability.
[0032] Furthermore, the dispersant is one of sodium polyacrylate and polyacrylic acid.
[0033] When sodium polyacrylate and polyacrylic acid are dissolved in water, they will ionize to form high molecular anions, which are adsorbed on the surface of dispersed particles. The polymer chain of sodium polyacrylate forms a high molecular film on the surface of the particles, which prevents the particles from approaching each other through the steric hindrance effect. In addition, in the present invention, aluminum-doped zinc oxide, N-doped titanium dioxide and acrylate can be better compatible, which is beneficial to the dispersion of inorganic particles.
[0034] Furthermore, the defoaming agent is at least one of polydimethylsiloxane and polyether defoaming agent.
[0035] Polydimethylsiloxane and polyether defoamers have low surface tension and can quickly spread on the air-liquid interface of the foam, destroying the stability of the foam, causing the foam liquid film to become thinner and eventually rupture. Bubbles may be generated in the slurry during stirring. By adding defoamers, the influence of bubbles on coating uniformity can be avoided and pits can be avoided after curing.
[0036] Furthermore, the solvent is a mixed solution of ethanol, dimethylformamide and water, and the mixing ratio is ethanol: dimethylformamide: water = (3-5): (2-4): 3 by mass ratio.
[0037] Since the raw materials contain multiple components such as organic and inorganic, the dissolution and blending of the raw materials can be promoted by blending multiple solvents. The proportion of solvents can be adjusted according to the proportion of different materials in the raw materials to ensure the best mixing effect.
[0038] Furthermore, the anti-blue light layer slurry is obtained by uniformly mixing raw materials according to mass percentage.
[0039] The present invention also provides an application of a protective film with a blue light protection function. The protective film prepared by the preparation method described above is used in the field of electronic devices such as mobile phones, computers and OLED screens.
[0040] Beneficial effects of the present invention:
[0041] (1) The present invention forms a laminated anti-blue light protective film by layer-by-layer coating and curing, including a wear-resistant layer, an anti-blue light layer, an adhesive layer and a release film, wherein the slurry of the anti-blue light layer is added with a blue light absorber mixed with aluminum-doped zinc oxide, N-doped titanium dioxide and diosgenin. The light absorption ranges of the three materials overlap and combine to absorb harmful blue light while retaining beneficial blue light, thereby reducing color deviation, thereby ensuring the safety of the protective film and avoiding a reduction in light transmittance.
[0042] (2) The present invention utilizes aluminum doping to achieve a red shift in the absorption edge of zinc oxide, and D doping to achieve the visible light response of titanium dioxide, thereby improving the absorption capacity of harmful blue light. By adjusting the mixing ratio with the natural organic substance diosgenin, the characteristics of the absorption peaks of different materials are combined to achieve enhanced absorption capacity for harmful blue light while retaining beneficial blue light, and accurately control the absorption band. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] Preparation of aluminum-doped zinc oxide:
[0046] Aluminum sulfate 18hydrate solution and zinc sulfate heptahydrate solution were mixed, and the mass of aluminum element in the obtained mixed solution was 0.5% of the mass of zinc element. Ammonia solution was added dropwise to the mixed solution under stirring at 70°C until the pH value of the system was 7.5. After the addition was completed, the mixture was allowed to react for 4 hours, filtered, washed, and dried, and ground to obtain aluminum-doped zinc oxide precursor powder, which was calcined at 1200°C for 8 hours to obtain aluminum-doped zinc oxide.
[0047] Preparation of N-doped titanium dioxide:
[0048] Titanium dioxide was dispersed in water with a titanium dioxide concentration of 0.1 g / mL, and urea was added with a molar ratio of titanium dioxide to urea of 1:1. After ultrasonic dispersion, it was heated to 250°C for reaction for 2 hours, cooled to room temperature, filtered and washed, and then dried and calcined at 350°C for 4 hours to obtain N-doped titanium dioxide.
[0049] Preparation of anti-blue light layer slurry:
[0050] Prepare the raw materials according to the following mass percentages:
[0051] 7% aluminum-doped zinc oxide, 2% N-doped titanium dioxide, 1% diosgenin, 15% 2-hydroxy-2-methyl-1-phenylpropanone, 4% sodium polyacrylate, 40% acrylate, 0.1% polydimethylsiloxane, and the remainder is a mixed solution of ethanol, dimethylformamide and water (mass ratio of ethanol: dimethylformamide: water = 3:4:3).
[0052] The above raw materials are stirred and mixed evenly to obtain a blue light protection layer slurry.
[0053] Preparation of protective film with anti-blue light function:
[0054] Step 1: coating the wear-resistant layer slurry on the upper surface of a PET film with a thickness of 70 μm, and obtaining a wear-resistant layer after curing, wherein the thickness of the wear-resistant layer is 10 μm;
[0055] Step 2: coating the anti-blue light layer slurry on the lower surface of the transparent substrate, and obtaining the anti-blue light layer after curing, wherein the thickness of the anti-blue light layer is 5 μm;
[0056] Step three: apply adhesive layer slurry on the surface of the anti-blue light layer, the thickness of the adhesive layer is 10 μm, and adhere a release film on the surface of the adhesive layer, the thickness of the release film is 100 μm, to obtain a protective film with anti-blue light function.
[0057] Example 2
[0058] The only difference from Example 1 is that when preparing aluminum-doped zinc oxide, the mass of aluminum element in the mixed solution is 0.8% of the mass of zinc element. Other steps and conditions are the same as in Example 1.
[0059] Example 3
[0060] The only difference from Example 1 is that when preparing aluminum-doped zinc oxide, the mass of aluminum element in the mixed solution is 1% of the mass of zinc element, and the other steps and conditions are the same as Example 1.
[0061] Example 4
[0062] The only difference from Example 2 is that the molar ratio of titanium dioxide to urea is 1:2 when preparing N-doped titanium dioxide, and the other steps and conditions are the same as Example 2.
[0063] Example 5
[0064] The only difference from Example 2 is that the molar ratio of titanium dioxide to urea is 1:3 when preparing N-doped titanium dioxide, and the other steps and conditions are the same as Example 2.
[0065] Example 6
[0066] The only difference from Example 4 is that the mass percentage of the raw materials is different when preparing the anti-blue light layer slurry, the solvent ratio is appropriately adjusted, and the other steps and conditions are the same as Example 4. The specific mass percentages are as follows:
[0067] 14% aluminum-doped zinc oxide, 4% N-doped titanium dioxide, 2% diosgenin, 10% 2-hydroxy-2-methyl-1-phenylpropanone, 8% sodium polyacrylate, 35% acrylate, 0.3% polydimethylsiloxane, and the remainder is a mixed solution of ethanol, dimethylformamide and water (mass ratio of ethanol: dimethylformamide: water = 4:3:3).
[0068] Example 7
[0069] The only difference from Example 4 is that the mass percentage of the raw materials is different when preparing the anti-blue light layer slurry, and the other steps and conditions are the same as Example 4. The specific mass percentages are as follows:
[0070] 15% aluminum-doped zinc oxide, 4.3% N-doped titanium dioxide, 2.2% diosgenin, 5% 2-hydroxy-2-methyl-1-phenylpropanone, 10% sodium polyacrylate, 30% acrylate, 0.5% polydimethylsiloxane, and the remainder is a mixed solution of ethanol, dimethylformamide and water (mass ratio of ethanol: dimethylformamide: water = 5:2:3).
[0071] Example 8
[0072] The only difference from Example 6 is that when preparing the anti-blue light layer slurry, the mass percentage of N-doped titanium dioxide in the raw material is increased to 5.5%, and the other steps and conditions are the same as Example 6.
[0073] Example 9
[0074] The only difference from Example 6 is that the mass percentage of N-doped titanium dioxide in the raw material is increased to 6% when preparing the anti-blue light layer slurry, and the other steps and conditions are the same as Example 6.
[0075] Example 10
[0076] The only difference from Example 8 is that the mass percentage of diosgenin in the raw material is increased to 2.5% when preparing the anti-blue light layer slurry, and the other steps and conditions are the same as Example 8.
[0077] Embodiment 11
[0078] The only difference from Example 8 is that the mass percentage of diosgenin in the raw material is increased to 3% when preparing the anti-blue light layer slurry, and the other steps and conditions are the same as Example 8.
[0079] Comparative Example 1
[0080] Compared with Example 1, the anti-blue light layer slurry in this comparative example replaces aluminum-doped zinc oxide with an equal amount of N-doped titanium dioxide, and other conditions and steps are the same as Example 1.
[0081] Comparative Example 2
[0082] Compared with Example 1, the anti-blue light layer slurry in this comparative example replaces N-doped titanium dioxide with an equal amount of aluminum-doped zinc oxide, and other conditions and steps are the same as Example 1.
[0083] Comparative Example 3
[0084] Compared with Example 1, the anti-blue light layer slurry in this comparative example replaces diosgenin with equal amounts of N-doped titanium dioxide and aluminum-doped zinc oxide (mass ratio 1:1), and other conditions and steps are the same as Example 1.
[0085] Performance tests were performed on Examples 1 to 11 and Comparative Examples 1 to 3, and the results are shown in Table 1.
[0086] Table 1
[0087]
[0088] As can be seen from Table 1, Example 2 adds aluminum doping compared to Example 1, and the absorption capacity of aluminum-doped zinc oxide for harmful blue light is enhanced, and the blocking rate is increased. Excessive aluminum doping in Example 3 causes the crystal form of aluminum-doped zinc oxide to change, and the effect of blue light absorption is significantly reduced. Example 4 increases the proportion of urea when N-doped titanium dioxide is added on the basis of the aluminum doping ratio in Example 2, and its blocking rate in the harmful blue light band is significantly improved on the technology of Example 2. In Examples 6 and 7, the proportion of blue light absorber in the anti-blue light layer slurry is gradually increased. With the increase of blue light absorber, the blocking rate of blue light is improved, but on the contrary, its transmittance will decrease. Considering the comprehensive performance, the proportion of Example 6 can ensure a higher ultraviolet and blue light blocking rate and visible light transmittance. In Example 8, the proportion of N-doped titanium dioxide in the blue light absorber is increased on the basis of the proportion in Example 6. Since its absorption band is concentrated in the range of 300-450nm, a proper increase can improve the blocking of harmful blue light and ultraviolet light. It has weak absorption ability in the 480-500nm band, and has little effect on its blocking rate, but too much N-doped titanium dioxide will cause overlapping aggregation between particles, which will have a negative impact on the transmittance. In Examples 10 and 11, the ultraviolet and blue light blocking performance of the protective film with increased diosgenin content is improved. In the absence of aluminum-doped zinc oxide in Comparative Example 1, the blocking rate of the protective film in the ultraviolet band of 320-400nm decreased significantly, and the replacement of N-doped titanium dioxide enhanced the absorption capacity of the 480-500nm band, resulting in color deviation problems. In the case of the lack of N-doped titanium dioxide in Comparative Example 2, the absorption capacity of the protective film in the ultraviolet and harmful blue light bands is reduced. In the case of the lack of diosgenin in Comparative Example 3, the blocking rate of the protective film in the 415-455nm band is reduced.
[0089] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0090] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a protective film with blue light protection function, characterized in that: The following steps are involved: Step 1: coating the wear-resistant layer slurry on the upper surface of the transparent substrate, and obtaining the wear-resistant layer after curing; Step 2: coating the anti-blue light layer slurry on the lower surface of the transparent substrate, and obtaining the anti-blue light layer after curing; Step 3: coating the surface of the anti-blue light layer with an adhesive layer slurry, and covering the surface of the adhesive layer with a release film to obtain a protective film with anti-blue light function; The anti-blue light layer slurry comprises the following raw materials by mass percentage: Aluminum-doped zinc oxide 7-15%, N-doped titanium dioxide 2-6%, diosgenin 1-3%, photoinitiator 5-15%, dispersant 4-10%, acrylate 30-40%, defoamer 0.1-0.5%, and the balance is solvent.
2. The method for preparing a protective film with blue light protection function according to claim 1, characterized in that: The preparation steps of the aluminum-doped zinc oxide are as follows: Aluminum sulfate 18hydrate solution and zinc sulfate heptahydrate solution were mixed, and ammonia solution was added dropwise to the mixed solution under constant temperature stirring until the pH value of the system was 7-7.
5. After the addition was completed, the mixture was allowed to react for 2-4 hours, filtered, washed, and dried, and ground to obtain aluminum-doped zinc oxide precursor powder, which was then calcined at high temperature to obtain aluminum-doped zinc oxide.
3. The method for preparing a protective film with blue light protection function according to claim 2, characterized in that: The mass of the aluminum element in the mixed solution is 0.5-1% of the mass of the zinc element.
4. The method for preparing a protective film with blue light protection function according to claim 2, characterized in that: The temperature of the constant temperature stirring is 70-80° C., the temperature of the high temperature calcination is 1000-1300° C., and the calcination temperature is 6-10h.
5. The method for preparing a protective film with blue light protection function according to claim 1, characterized in that: The preparation steps of the N-doped titanium dioxide are as follows: Titanium dioxide is dispersed in water, urea is added, and after ultrasonic dispersion, it is heated to 200-250° C. and reacted for 2-4 hours. The mixture is cooled to room temperature, filtered, washed, dried, and calcined at high temperature to obtain N-doped titanium dioxide.
6. The method for preparing a protective film with blue light protection function according to claim 5, characterized in that: The molar ratio of titanium dioxide to urea is 1:1-3.
7. The method for preparing a protective film with blue light protection function according to claim 5, characterized in that: The calcination temperature is 300-600° C., and the calcination time is 1-4 hours.
8. The method for preparing a protective film with blue light protection function according to claim 1, characterized in that: The photoinitiator is one of 2-hydroxy-2-methyl-1-phenylpropanone, 2,2-dimethoxy-2-phenylacetophenone, and 2,2-dimethoxyacetophenone; The dispersant is one of sodium polyacrylate and polyacrylic acid; The defoamer is at least one of polydimethylsiloxane and polyether defoamer; The solvent is a mixed solution of ethanol, dimethylformamide and water, and the mixing ratio is ethanol: dimethylformamide: water = (3-5): (2-4): 3 by mass.
9. The method for preparing a protective film with blue light protection function according to claim 1, characterized in that: The anti-blue light layer slurry is obtained by uniformly mixing raw materials according to mass percentage.
10. Application of a protective film with blue light protection function, characterized in that: The protective film prepared by the method for preparing a protective film with anti-blue light function as described in any one of claims 1 to 9 is used in the field of electronic devices such as mobile phones, computers and OLED screens.
Citation Information
Cited By
Protective film with eye protection function
CN224702692U